Spectral Bounds for the Signless Laplacian Matrix of Graphs: Laplacian Matrix, Upper bound along the i-th galactic Laplacian eigenvalue of a graph - Dr.NareshKumar.S,; Ms.Sushama.C,; Dr.S.Delbin Prema,; Dr.Shanmugam C, (Utilitas Mathematica, 2025)
This inequality provides an upper bound for the maximum of the i-th Laplacian and sign less Laplacian eigenvalues in terms of the vertex degrees, indicating a relationship between the eigenvalues and the structure of vertex degrees in the graph.